Blood biochemical parameters during bovine endotoxemia and after i/v infusion of hypertonic saline and plasmex-D-40 - SINGH, D V; SINGH, R V; SODHI, S P S (The Indian Journal of Animal Sciences, 2014)
Two groups of 5 animals each were subjected to endotoxic shock to investigate the biochemical effects of i/v infusion of hypertonic saline and dextran-40 by i/v infusion of E. coli endotoxin @ 5 mg/kg bw/hr for 3 hr. Group 1 animals which were left untreated afterwards and were observed for next 4 hr showed a significant (P